2016
DOI: 10.1097/md.0000000000003207
|View full text |Cite
|
Sign up to set email alerts
|

70% Alcohol Versus Dry Cord Care in the Umbilical Cord Care

Abstract: Recently the use of antibacterial agents to clean and dry the stump of the newborns’ umbilical cord (UC) after birth has been abandoned by many neonatal units in favor of dry cord care. Aim of this study was to compare the occurrence of adverse events (AEs) and time to cord separation among newborns treated with dry cord care versus 70% alcohol in an Italian Academic Hospital (AH).From December 2014 to March 2015, 239 infants were born at the AH. The number of eligible infants was 200 and they were equally ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 21 publications
3
19
1
1
Order By: Relevance
“…6,10,23 Before the umbilical cord separates from the infant, the remaining stump can be considered as undergoing the wound healing healing and thus becomes a route for infection to enter the baby's bloodstream through the blood vessels. 9,14,17 Poor umbilical cord care will delay umbilical cord separation. 13 Delayed umbilical cord separation can increase the risk of infection.…”
Section: Day 3 Day 1 After Cord Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…6,10,23 Before the umbilical cord separates from the infant, the remaining stump can be considered as undergoing the wound healing healing and thus becomes a route for infection to enter the baby's bloodstream through the blood vessels. 9,14,17 Poor umbilical cord care will delay umbilical cord separation. 13 Delayed umbilical cord separation can increase the risk of infection.…”
Section: Day 3 Day 1 After Cord Separationmentioning
confidence: 99%
“…7,8 Since 1998, WHO has recommended that umbilical cord care in newborns should be performed in a clean and dry manner. 9,10 Likewise, the Indonesian Ministry of Health also recommends open and dry cord care for newborns. 11 Umbilical cord is the area that is most susceptible to bacteria colonization that may lead to neonatal infections such as sepsis and omphalitis due to its necrotic property.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size required for this study was calculated using the following formula and based on a study by Taffazoli et al (11) and with a confidence level of 95% and α= 0.05 and β=0.2…”
Section: Sample Sizementioning
confidence: 99%
“…In the 21st century there have been several studies on umbilical cord (UC) care comparing different antiseptics, and several studies have shown that the hygiene habits of bathing and drying it were not associated with an increased risk of omphalitis when compared to alcohol application 4 - 6 . Topical triple dye is a treatment used in the United States, and there are several studies comparing the topical triple dye with alcohol application for UC care, and the results of these studies show that there are no differences between the treatment groups of omphalitis( 7-8) .…”
Section: Introductionmentioning
confidence: 99%